Gonadosomatic index and fecundity of Heteropneustes fossilk (Bloch) (Pisces : Heteropneustidae) from Hussain Sagar, Hyderabad - Reddy, Y Siva; Rao, M Babu (Indian Journal of Fisheries, 2011)
The gondosomatic index of the specimens of Heteropneustes fossiles (Bloch) from Hussain Sagar lake, Hyderabad, indicated their spawning season from April to July. Fecundity ranged from 1 446 to 30 050. This was less than the specimens of Cultack and Barrackpore but more than those of Kolleru lake. No positive correlation was noticed between the total length or the weight of the fish and fecundity. The specimens of Hussun Sagar (length range 150- 340 mm) took more time to attain maturity than those of Kolleru lake (length range 100 - 260 mm).